Glucosides and urea derivatives from the seeds of Scaphium macropodum (Miq.) Beumée - Tu, Vu Anh; Diep, Chau Ngoc; Phan, Nguyen Huu Toan; Duy, Nong Van; Thuan, Nguyen Thi Dieu; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Minh, Chau Van (Vietnam Journal of Science and Technology, 2016)
Five known compounds {carbonylbis[imino(6-methyl-3,1-phenylenel)]}bis[carbamic acid] dimethyl ester (1), (1'R,3'S,5'R,8'S,2E,4E-dihydrophaseic acid) 3'-O-beta-D-glucopyranoside (2), 3-methylbutan-1-ol beta-D-glucopyranoside (3), astragalin (4) and daucosterol (5) were isolated from the methanol extract of the seeds of Scaphium macropodum (Miq.) Beumée. The structures of the isolated compounds were elucidated by the spectroscopic methods including NMR and MS, and also by comparison with the literature data. Compounds 1-3 were isolated from this plant for the first time.